Reframing the wicked problem of pre-harvest burning: A case study of Thailand's sugarcane - Wirawat Chaya (Heliyon, 2024)
Pre-harvest sugarcane burning persists in many countries though there are policies prohibiting the practice. As problems related to sugarcane harvesting are complex, a thorough understanding of the problems for policy formulation is required. The objective of this study was to reanalyze or reframe problems of sugarcane harvesting and pre-harvest sugarcane burning. Concepts of wicked problems, practical reasoning and policy reframing were applied. The study used a participatory modeling approach to illustrate the case of Thailand. Wickedness was shown by complexity and uncertainties of factors intertwining with values related to adoption of harvesting methods; green mechanical, green manual and burnt manual. As timeliness of harvest was the top priority, the burnt method was considered more efficient. It was easier, faster, cheaper and more suitable under unfavorable circumstances for the green methods. The policy to reduce burnt-harvested sugarcane was not so effective and also led to the undesired ‘green but unclean’ method. To frame harvesting problems based on emissions of fine particulates (PM2.5) from sugarcane burning was not a good choice. Incomplete problem sense-making and poor problem frame were indicated. Most farmers were unable to associate sugarcane burning with environmental problems of PM2.5 (and also global warming/climate change) and livelihood impacts. Nevertheless, a larger concern over climate variations was perceived by a majority of farmers. Farmers who adapted relied primarily on green harvesting and the use of residues as trash blankets. Through policy reframing, inefficient green harvesting was seen as a better frame. The new frame enabled farmers linking agricultural practices to sustainability of environment, productivity and livelihoods in the context of climate change. Using participatory modeling for reframing policy problems in general and wicked problems in particular was shown to be powerful and contributing to originality.